A cost-effectiveness analysis of sotorasib as second-line treatment for patients with KRAS-G12C-mutated metastatic non-small cell lung cancer (mNSCLC) in Switzerland (Swiss Medical Weekly, 2025)
BACKGROUND AND OBJECTIVE: Because of the lack of effective targeted treatment options, docetaxel has long been the standard second-line therapy for patients with advanced non-small cell lung cancer, including the Kirsten rat sarcoma virus (KRAS) G12C mutation. The CodeBreak 200 trial demonstrated that sotorasib, a new drug targeting the G12C-mutated KRAS protein, modestly improved progression-free survival compared with docetaxel in patients whose cancer had progressed after receiving platinum chemotherapy and programmed cell death protein 1 (PD-1) / programmed death ligand 1 (PD-L1) inhibitors as first-line treatment. Consequently, sotorasib received temporary approval in Switzerland.Our analysis assessed the cost-effectiveness of sotorasib as a second-line treatment in Swiss patients with non-small cell lung cancer from the perspective of the Swiss statutory health insurance system.METHODS: A partitioned survival model based on the CodeBreak 200 trial was constructed with a time horizon of 10 years and a discount rate of 3% for costs and quality-adjusted life years (QALYs). Parametric survival curves were fitted to the published Kaplan-Meier data, and survival was extrapolated. QALYs were obtained from the CodeBreak 100 trial and the literature. The costs of drugs, drug administration, diagnostics, disease management, and adverse events were considered. Because the price of sotorasib has not been established in Switzerland, two scenarios were analysed: the first used the published expected monthly United Kingdom (UK) price in Swiss francs (CHF 7870); the second used one-quarter of that price (CHF 1968), according to the lower dose used in the most recent trial, under the condition that one-quarter of the original sotorasib dose is equally effective. Treatment costs of adverse events were included.RESULTS: Log-normal functions best fitted the survival curves from CodeBreak 200. For sotorasib versus docetaxel, our estimation showed no difference in QALYs (1.28 QALYs for both treatments), as the reduced adverse events reported in CodeBreak 200 for sotorasib had a minimal impact on the QALYs in our calculation. This made an incremental cost-effectiveness ratio (ICER) calculation irrelevant. Total per-patient costs were CHF 138,894 for the full sotorasib dose, CHF 82,741 for the one-quarter dose, and CHF 80,383 for docetaxel. These results were robust in 99% of probabilistic simulations.CONCLUSION: Sotorasib did not demonstrate cost-effectiveness at the full dosage nor when reduced to a quarter of the dose. The primary factors motivating clinicians to prescribe sotorasib are its superior overall response rate compared with docetaxel and the reported improvement in patients’ quality of life. These factors suggest that it would be reasonable to price it at approximately one-quarter of the assumed cost in the UK.